A degenerate population system: Carleman estimates and controllability. (June 2020) - Boutaayamou, Idriss; Fragnelli, Genni
Abstract: In this paper we consider a system in non divergence form which models the interaction between two different species u and v . Both of them depend on time, on age and on space. Moreover, the diffusion coefficients degenerate at the boundary of domain. We study, in particular, null controllability of the system via observability inequalities and Carleman estimates for the associated non homogeneous adjoint problem.